ACCOUNTABILITY DISCLOSURE OF WEB-BASED AND PSAK 109 ZAKAT MANAGEMENT ORGANIZATIONS - Narulitasari, Devi; Piliyanti, Indah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to determine the level of disclosure of web-based accountability and PSAK 109 of zakat management organizations in Indonesia. The type and research approach used is descriptive research. This research uses secondary data obtained from the official website of each zakat management institution in Indonesia in 2023, consisting of 35 Amil Zakat Agencies and 117 Amil Zakat Institutions, thus obtaining a sample of 25 Amil Zakat Bodies and 98 Amil Zakat Institutions. Data analysis carried out using content analysis consisting of 2 stages. The first stage is to carry out a checklist on the website with disclosure and dialogue criteria. The second stage is to conduct a content analysis of PSAK 109's suitability in the financial statements. The research results show that the average website-based accountability disclosure at the National Amil Zakat Agency is in the middle category and at the Amil Zakat Institution is in the high category. Meanwhile, the average accountability disclosure by PSAK 109 at the Amil Zakat Agency is in the very low category and the Amil Zakat Institution is in the very low category. This shows that zakat management organizations need to prepare financial reports by PSAK 109 and publish them via the website to increase their accountability to the public. Keywords: disclosure, accountability, website, financial reports, PSAK 109.